2017
DOI: 10.3390/toxins9060185
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1 Tolerance and Accumulation in Black Soldier Fly Larvae (Hermetia illucens) and Yellow Mealworms (Tenebrio molitor)

Abstract: Crops contaminated with fungal mycotoxins such as aflatoxin B1 (AFB1) are often downgraded or removed from the food chain. This study aimed to evaluate the tolerance and accumulation of AFB1 in two insect species to determine whether they could be used to retain condemned mycotoxin contaminated crops in the food chain. First, instar black soldier fly larvae (Hermetia illucens, BSF) and yellow mealworm (Tenebrio molitor, YMW) were fed poultry feed spiked with AFB1 and formulated to contain levels of 0.01, 0.025… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
127
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(146 citation statements)
references
References 31 publications
11
127
8
Order By: Relevance
“…Bosch, van der Fels‐Klerx, De Rijk, and Oonincx () investigated the aflatoxin B 1 (AFB 1 ) tolerance and accumulation in larvae of H. illucens and T. molitor . They found that the AFB 1 concentrations tested for (at levels of 0.01, 0.025, 0.05, 0.10, 0.25, and up to 0.5 mg/kg dry feed) did not affect survival and weight gains in both species.…”
Section: Chemical Hazardsmentioning
confidence: 99%
“…Bosch, van der Fels‐Klerx, De Rijk, and Oonincx () investigated the aflatoxin B 1 (AFB 1 ) tolerance and accumulation in larvae of H. illucens and T. molitor . They found that the AFB 1 concentrations tested for (at levels of 0.01, 0.025, 0.05, 0.10, 0.25, and up to 0.5 mg/kg dry feed) did not affect survival and weight gains in both species.…”
Section: Chemical Hazardsmentioning
confidence: 99%
“…Arthropods are very diverse in their interactions with toxigenic molds, ranging from high susceptibility to remarkable tolerance, presumably, resulting from the variable nature of this evolutionary pressure across habitats. Variation in susceptibility to AF and other mycotoxins has been detected by various studies focusing on mycophagous mites (Racovitza, 2009), Drosophila species (Rohlfs and Obmann, 2009), soldier fly larvae (Hermetia illucens) (Bosch et al, 2017;Camenzuli et al, 2018), the maize weevil (Sitophilus zeamais) (Drott et al, 2017), the yellow and lesser mealworms (Tenebrio molitor and Alphitobius diaperinus) (Bosch et al, 2017;Camenzuli et al, 2018), the navel orangeworm (Amyelois transitella) (Niu et al, 2009), the cabbage looper (Trichoplusia ni) (Zeng et al, 2013), or the corn earworm (Helicoverpa zea) (Zeng et al, 2006;Niu et al, 2008Niu et al, , 2009. It is plausible that species feeding on highly contaminated food sources are selected towards higher tolerance.…”
Section: The Aspergilli and Their Mycotoxins Versus Arthropodsmentioning
confidence: 99%
“…In the growing stage, the larval biomass contained considerable DON concentration; however, there was no DON accumulation observed in BSFL after the 12-day rearing. Bosch et al [3] evaluated the tolerance and accumulation of aflatoxin B1 (AFB1) in BSFL fed with AFB1-containing feeds to utilize the mycotoxin-contaminated crops. The BSFL did not contain detectable levels of AFB1 (<0.10 µg/kg).…”
Section: Amounts Of Don In Spent Feed and Bsfl Biomassmentioning
confidence: 99%
“…In order to limit the mycotoxins in food and feed, regulations specify maximum allowable concentrations, which is 1 mg/kg sample in many countries. According to the regulations, products are monitored, and when mycotoxin concentrations exceed the maximum allowable limits, products are separated from the food chain [3]. The economic loss from FHB accounts for many millions of dollars in Canada alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation